Intrusiones Mutuas. Metálogo con Roger Bartra - Elhaik, Tarek (Revista de Antropología Social, 2008)
“Mutual Intrusions” explores the personal trajectory of Roger Bartra, leading Mexican anthropologist and polemical public intellectual figure in contemporary Mexico. It is a portrait of a fellow anthropologist playfully working and producing eroticized cartographies of the boudoir he dwells in-Mexico-the “peep show” as he calls it. In the form of a Batesonian metalogue, the conversation meanders through Bartra’s oeuvre as a passage across affective, aesthetic and literary landscapes that troubles the cultural politics and poetics of the Writing Culture paradigm.